Nasal respiration modulates pain perception via the olfactory bulb-anterior cingulate cortex circuit - Cheng, Ruixue; Wang, Yuxue; Dou, Chunyan; Gu, Song; Tang, Weixiang; Chen, Chen; Chen, Ke; Cui, Shuai; Zhong, Weiwei (iScience, 2025)
Breath regulation has been shown to reduce pain and anxiety-like emotions in humans, but the underlying neural mechanisms are still unclear. Here, we demonstrate that nasal respiratory sensory deprivation (Triton X-100) reduces the respiration-entrained rhythm (RR) transmitted from the olfactory bulb (OB) to the anterior cingulate cortex (ACC), ultimately exerting an antinociceptive effect in a mouse model of neuropathic pain. Specifically, optogenetics, in vivo fiber photometry, viral tracing, and immunofluorescence staining revealed that nasal respiratory sensory deprivation activates GABAergic projections from the OB to the ACC and inhibits glutamatergic (Glu) neurons in the ACC. Chemogenetic activation or inhibition of the OB-ACCGlu pathway leads to nociceptive hypersensitivity or exerts antinociceptive effects, respectively. Similarly, the activation or inhibition of ACC-projecting OBGABA neurons reduces neuropathic pain or induces nociceptive sensitization. Taken together, our findings offer new insights into therapeutic approaches for pain relief through nasal breathing.